Comparison of Fatal Injuries Resulting from Tractor and High Speed Motorcycle Accidents in Turkey: A Multicenter Study - Suna Eraybar; Serhat Atmaca; Yasemin Nennicioglu; Gokhan Torun; Okan Aydin; Behçet Varisli; Nuran Sandal; Tunç Buyukyilmaz; Murat Seyit; Harun Yildirim; Erol Armagan (Emergency Medicine International)
Aim. Injuries are among the main causes of mortality and morbidity all over the world, and effective initial triage of these patients can determine the thin line between death and life. Tractor accidents and related injuries are significant problems particularly in rural areas. However, major trauma classification systems do not include tractor accidents as a criterion for trauma team activation or transportation of the patients to a trauma center. This study evaluated the general characteristics and outcomes of tractor accidents in comparison to motorcycle accidents, which are considered as a comparison criterion for major trauma. Materials and Methods. This is a multicenter study conducted in 6 emergency departments in 4 cities over a six month period. All cases over 18 years of age who were admitted to emergency service due to tractor or motorcycle accidents and meet the criteria were included in the study. The general characteristics and outcomes of both trauma types were compared to determine whether tractor accident should be considered as major traumas. Results. Eighty-eight patients had a tractor accident, and 339 patients had a motorcycle accident. The tractor accident victims were significantly younger (p<0.001), and the proportion of females was higher in this group (p=0.001). Glasgow coma score (p=0.062), revised trauma score (p=0.201), duration from incident to admission (p=0.481), and route of admission (p=0.810) were similar between both accident types. The rates of thoracic traumas (42% versus 23%, p<0.001) and spinal injuries (17% versus 5.9%, p=0.002) were significantly higher in tractor accidents. The hospitalization rates of the patients were significantly higher in tractor accidents (p=0.008). Conclusion. The findings of this study support the hypothesis that tractor accidents should be included in the criteria of ATLS major trauma classification system and trauma team activation procedures.